STRATEGI PEMASARAN BUAH MELON HIDROPONIK (Studi Kasus Di Rasidin Veggies House, Kecamatan Patrang, Kabupaten Jember) - Farras Zalikhah Zahra; Muh. Taufiek Heryansah; Mulia Annisa Rahma; Ratih Apri Utami (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
This study aims to 1) explain the melon cultivation in Rasidin Vegies House, 2) identify the marketing mix strategy in Rasidin Vegies House, 3) analyze the marketing strategy using SWOT framework. The method used to determine the research location is purposive method. The research is located at Rasidin Vegies House, Patrang Sub-district, Jember District. This research used descriptive qualitative methods with case study techniques. The data obtained through are observation, in depth interview, and documentation.The result showed that 1)Rasidin Vegies House cultivates Honey Globe melon varieties with hydroponic drip irrigation system, 2) the 4P of marketing mix apllied are price, promotion, place, and product, 3) based on SWOT analysis gained are internal factors (strenght and weakness) and external factors (opportunity and threats). First, the strenght of Rasidin Vegies House’s cultivation is using hydroponic system. Second, the weakness found that is climatic condition in green house still haven’t optimal.Then, the opportunity is high-yielding variety in cultivation. But, this melon production has threat in market demand stock.